Unravelling the Interactions between Hydrolytic and Oxidative Enzymes in Degradation of Lignocellulosic Biomass by Sporothrix carnis under Various Fermentation Conditions - Olusola A. Ogunyewo; Folasade M. Olajuyigbe (Biochemistry Research International)
The mechanism underlying the action of lignocellulolytic enzymes in biodegradation of lignocellulosic biomass remains unclear; hence, it is crucial to investigate enzymatic interactions involved in the process. In this study, degradation of corn cob by Sporothrix carnis and involvement of lignocellulolytic enzymes in biodegradation were investigated over 240 h cultivation period. About 60% degradation of corn cob was achieved by S. carnis at the end of fermentation. The yields of hydrolytic enzymes, cellulase and xylanase, were higher than oxidative enzymes, laccase and peroxidase, over 144 h fermentation period. Maximum yields of cellulase (854.4 U/mg) and xylanase (789.6 U/mg) were at 96 and 144 h, respectively. Laccase and peroxidase were produced cooperatively with maximum yields of 489.06 U/mg and 585.39 U/mg at 144 h. Drastic decline in production of cellulase at 144 h (242.01 U/mg) and xylanase at 192 h (192.2 U/mg) indicates that they play initial roles in biodegradation of lignocellulosic biomass while laccase and peroxidase play later roles. Optimal degradation of corn cob (76.6%) and production of hydrolytic and oxidative enzymes were achieved with 2.5% inoculum at pH 6.0. Results suggest synergy in interactions between the hydrolytic and oxidative enzymes which can be optimized for improved biodegradation.